Edukasi pada Ibu Hamil tentang Covid-19 di Kelurahan Thehok Kota Jambi - Hesty Hesty (Jurnal Abdimas Kesehatan (JAK), 2021)
Health is a need of every human being, this can only be achieved if the community, both individually and in groups, participates in increasing their ability to live a healthy life. Currently, positive cases of COVID-19 have existed in all provinces in Indonesia (34 Provinces). The COVID-19 pandemic has an impact on various problems, namely the status of public health, economy, education, the socio-cultural conditions of the community including the stigma about COVID-19 which causes discrimination, security problems. The health condition of prospective mothers during early pregnancy will affect the success rate of pregnancy and the condition of the health status of the prospective baby who is still in the womb or who has already been born, so it is recommended that the prospective mother can maintain a healthy lifestyle and avoid factors that can affect the condition of the prospective mother during pregnancy. This community service activity was carried out at RT 16 Kelurahan Thehok which is located on Jalan Adityawarman, South Jambi District, Jambi City. This activity was carried out in January 2021. The service method used a survey, lecture, and discussion approach. The results achieved were health education about the implementation of the Covid-19 health protocol to pregnant women when they were outside the home, especially in crowded places and this could be understood and carried out by pregnant women when they were outside the home and in crowded places and giving masks and covid-guidebooks. 19